Integrative Learning in US Undergraduate Public Health Education: A Review of Student Perceptions of Effective High-Impact Educational Practices at Georgia State University - Armstrong-Mensah, Elizabeth; Ramsey-White, Kim; Alema-Mensah, Ernest (Frontiers in Public Health, 2019)
In 2003, the United States (US) Institute of Medicine of the National Academies recommended the establishment of undergraduate public health programs to assist the public health workforce educate the public on health issues. In line with this recommendation, and that of the Consensus Conference on Undergraduate Public Health Education, Georgia State University established a Bachelor of Science in Public Health (BSPH) program in 2016, with the mission of advancing health through leadership, scholarship, research, and service, to better the human condition and to promote the common good, especially for urban communities in the US and for global populations. Using integrative approaches that encourage student empowerment and self-development, and which seek to equip students with the requisite knowledge and skills to be integrative thinkers, critical and analytical problem solvers, and reflective learners, the Georgia State University BSPH program currently offers a range of generalist introductory public health courses to over 400 students. This review seeks to examine the integrative practices utilized by Georgia State University faculty in its BSPH program and to investigate the extent to which these integrative educational practices prepare students to use insights gained in the classroom and from the field, to question, modify, connect, and integrate material learned in the academic setting, to real-life public health challenges. It also seeks to identify which of the integrative educational practices have the highest impact of helping students integrate the knowledge and skills gained to public health issues.